2008
DOI: 10.1086/533582
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Simulations of Standing Accretion Shock Instability in Core‐Collapse Supernovae

Abstract: We have studied nonaxisymmetric standing accretion shock instabilities, or SASI, using three-dimensional (3D) hydrodynamical simulations. This is an extension of our previous study of axisymmetric SASI. We have prepared a spherically symmetric and steady accretion flow through a standing shock wave onto a protoYneutron star, taking into account a realistic equation of state and neutrino heating and cooling. This unperturbed model is meant to represent approximately the typical postbounce phase of core-collapse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
218
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 135 publications
(226 citation statements)
references
References 27 publications
6
218
2
Order By: Relevance
“…A fourth group has used a version of the Zeus-MP code (Hayes et al 2006;Iwakami et al 2008Iwakami et al , 2009a for hydrodynamics and the IDSA scheme for neutrino transport (Liebendörfer et al 2009), which we will refer to as "Zeus +IDSA." Zeus+IDSA is fully Newtonian and the transport omits inelastic (energy exchanging) scattering in favor of the elastic versions.…”
Section: Other Axisymmetric Simulationsmentioning
confidence: 99%
“…A fourth group has used a version of the Zeus-MP code (Hayes et al 2006;Iwakami et al 2008Iwakami et al , 2009a for hydrodynamics and the IDSA scheme for neutrino transport (Liebendörfer et al 2009), which we will refer to as "Zeus +IDSA." Zeus+IDSA is fully Newtonian and the transport omits inelastic (energy exchanging) scattering in favor of the elastic versions.…”
Section: Other Axisymmetric Simulationsmentioning
confidence: 99%
“…A number of early 3D simulations utilized the smoothed-particle hydrodynamics approximation (Fryer & Warren 2002, 2004Fryer & Young 2007), which has certain disadvantages over grid-based codes (see, e.g., Plewa 2001;Agertz et al 2007;McNally et al 2012;Sijacki et al 2012). Studies of the SASI have made various approxima-tions to achieve 3D simulations (Blondin & Mezzacappa 2007;Iwakami et al 2008Iwakami et al , 2009Fernández 2010). Simulations neglecting the effects of neutrinos and employing a simplified equation of state (EOS) have been used to study the amplification of magnetic fields in 3D (Endeve et al 2010(Endeve et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…For low-mass progenitors with O-NeMg core, the neutrino mechanism works successfully to explode in one-dimensional (1D) simulations because of the tenuous envelope (Kitaura et al 2006). For more massive progenitors with iron core, multi-dimensional (multi-D) effects such as neutrino-driven convection (e.g., Bethe 1990;Herant et al 1994;Burrows et al 1995;Janka & Müller 1996;Müller & Janka 1997) and the standing-accretion-shock-instability (SASI, Blondin et al 2003;Foglizzo et al 2006;Foglizzo et al 2007;Ohnishi et al 2006;Blondin & Mezzacappa 2007;Iwakami et al 2008;Iwakami et al 2009;Fernández & Thompson 2009;Hanke et al 2012; 2012; Couch 2013;Fernández et al 2014, see Foglizzo et al 2015 for a review) have been suggested to help the onset of the neutrino-driven explosion. Recently this has been confirmed by a number of self-consistent two-(2D) and three-dimensional (3D) simulations (e.g., Buras et al 2006;Ott et al 2008;Marek & Janka 2009;Bruenn et al 2013;Suwa et al 2010;Suwa et al 2014;Müller et al 2012a;Müller et al 2013;Takiwaki et al 2012;Takiwaki et al 2014;Hanke et al 2013;Dolence et al 2014;Bruenn et al 2014;Müller & Janka 2014, see Mezzacappa et al 2015Burrows 2013;Kotake et al 2012 for recent review)).…”
Section: Introductionmentioning
confidence: 99%